DINAMIKA SEJARAH PENDIDIKAN ISLAM DI INDOSESIA : DARI MASA KLASIK HINGGA MODERN - SARI ANGGREINI; LAYLA LAYLA; UNAISAH SOEHARDIN; AISYAH AISYAH; RIKY SUPRATAMA; HUSNA NASHIHIN (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
This study aims to examine the dynamics of Islamic religious education in Indonesia from the classical to the modern era. The purpose is to understand how Islamic education has evolved in line with social, political, and cultural developments across different historical periods. The research uses a qualitative descriptive method, focusing on literature analysis from academic sources related to Islamic education. The findings show that in the classical era, Islamic education was centered in mosques and traditional boarding schools, emphasizing memorization and religious sciences. In the transitional and modern periods, there were significant developments in curriculum, institutional structure, and teaching methods. Islamic education began to integrate general sciences and respond to modern educational challenges while still maintaining its core religious identity. In the modern era, pesantren and madrasah adopted formal systems, curriculum reform, and technological tools to improve learning quality. This transformation reflects the adaptability of Islamic education to changing times without losing its foundational values. The study concludes that Islamic education in Indonesia continues to be a relevant and evolving system that balances tradition and modernity.